2003
DOI: 10.2527/2003.812512x
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration in stressed ruminants may be the result of acortisol-induced diuresis1

Abstract: The effect on water and electrolyte balance of stress, simulated by intravenous infusion of cortisol, was studied using 24 18-mo-old Merino wethers (37.0 +/- 0.94 kg mean body weight [BW]) over 72 h. The sheep were allocated to one of four groups: 1) no water/no cortisol (n = 6); 2) water/no cortisol (n = 4); 3) no water/cortisol (n = 6); and 4) water/cortisol (n = 4). Animals allocated to the two cortisol groups were given 0.1 mg x kg BW(-1) x h(-1) of hydrocortisone suspended in isotonic saline to simulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 33 publications
8
36
0
6
Order By: Relevance
“…Kataria and Kataria (2007), in accordance with the results of our research, reported a significant increase in the concentration of cortisol in Marwari sheep, fed ad libitum and subjected to water deprivation for eight days; while Parker et al (2003) found that such experimental conditions do not activate the HPA (hypothalamus-pituitaryadrenal) axis in Merino sheep undergoing water deprivation for three days, and suggested that an increase in plasma cortisol represents a response to a longer period of water restriction. Parrot et al (1996) similarly observed a lack of cortisol release in sheep after feed and water restriction for 48 h.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Kataria and Kataria (2007), in accordance with the results of our research, reported a significant increase in the concentration of cortisol in Marwari sheep, fed ad libitum and subjected to water deprivation for eight days; while Parker et al (2003) found that such experimental conditions do not activate the HPA (hypothalamus-pituitaryadrenal) axis in Merino sheep undergoing water deprivation for three days, and suggested that an increase in plasma cortisol represents a response to a longer period of water restriction. Parrot et al (1996) similarly observed a lack of cortisol release in sheep after feed and water restriction for 48 h.…”
Section: Discussionsupporting
confidence: 80%
“…Cortisol plays an important role in maintaining the water balance and plasma electrolytes, although its mechanism of action is not yet clear (Parker et al 2003). Kataria and Kataria (2007), in accordance with the results of our research, reported a significant increase in the concentration of cortisol in Marwari sheep, fed ad libitum and subjected to water deprivation for eight days; while Parker et al (2003) found that such experimental conditions do not activate the HPA (hypothalamus-pituitaryadrenal) axis in Merino sheep undergoing water deprivation for three days, and suggested that an increase in plasma cortisol represents a response to a longer period of water restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In many related studies on other species, the test subjects avoid dehydration altogether during drought periods of average length for the area (King and Bradshaw, 2010;Brown et al, 2011). In cases where dehydration does occur, avoiding release of glucocorticoids could be beneficial as CORT release can increase energy expenditure and water loss (Parker et al, 2003), which would have the potential to worsen resource imbalances. While the trend across taxa is interesting, currently there are insufficient data that test whether the environmental conditions of a species' natural habitat has an effect on endocrine responses to dehydration.…”
Section: Corticosteronementioning
confidence: 99%
“…In such cases, it is difficult to differentiate if loss ob body weight reflects changes in feed intake or changes in body water. Many authors showed that most of the live weight losses during dehydration were accounted for body water loss in small ruminants [12] result of a cortisol induced diuresis in stressed animals by water scarce [12].…”
Section: Discussionmentioning
confidence: 99%